â€œProfil Usaha â€˜Sop Buah Icaâ€™ Di Boulevard Manadoâ€ â€œBusiness Profile of â€˜Sop Buah Icaâ€™ in Boulevard Manadoâ€ - Nesly Rumapea; Agnes E. Loho; Lyndon R.J. Pangemanan (COCOS, 2015)
ABSTRACTThis objective of this research is to determine the business profile of ‘Sop Buah Ica’ in terms of raw materials, capital, labor, production, business management, as well as the profit.The research was conducted for three months from March 2015 until May 2015. The data used are primary data and secondary data obtained directly from the business owner through interviews, and analyzed descriptively in the form of tables and figures.The research results showed that ‘Sop Buah Ica’ is categorized as small enterprise with their own equity, that employed 7 workers with the core business is selling beverages as the main product, and also foods.Fruit soup dominates the number of beverages types, the rest is juices and shaved ices. Fruit soup is the most favorable beverages, that availabe in 12 kinds, that are Avocado fruit soup, Soursoup fruit soup, Manggo fruit soup, Durian fruit soup, Just durian, Avocado Durian, Grape fruit soup, Strawberry fruit soup, Apple fruit soup, Melon fruit soup, Jackfruit fruit soup, and Watermelon fruit soup. The most favorable fruit soup is the Avocado fruit soup. ’Sop Buah Ica’ offers two kind of portions, which are regular and large (Banget). The main ingredients are the fruits that mostly supplied from Manado area and Minahasa. The business operates everyday except Sunday, with the majority of eating on the spot consumers, and also there are consumers that order take-away or delivery. According to the analyzing result of March 2015, ‘Sop Buah Ica’ had obtained profit with the ratio R/C of 1,25, therefore this business is feasible to develop.Keywords: business profile, fruit soup, profits